Sea-houses: Excavation of E and F Areas (LANX. Journal of the Scuola di Specializzazione in Beni Archeologici - Università degli Studi di Milano, 2013)
The eastern district, in the southern bay in the promontory of Nora, consists of six areas (A-F), separated by houses and public spaces. It is a clear example of the changes that the city of Nora has undergone since the Punic period untill the late antiquity. In fact, the first construction dates back to the Punic period. Then, in the imperial age, a first change is witnessed by the construction of private buildings. Further changes date back to the turn of the II century AD and the III century AD, and between the end of the IV century AD and the beginning of the V century AD, following the construction of two major roads, the E-F and G-K.
Keywords: Nora; southern cove; eastern district; domus F; domus E; main courtyard